The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1590/s0100-204x2013001200006
|View full text |Cite
|
Sign up to set email alerts
|

Abordagens semiquantitativa e quantitativa na avaliação da textura do solo por espectroscopia de reflectância bidirecional no VIS-NIR-SWIR

Abstract: Resumo -O objetivo deste trabalho foi avaliar o potencial da espectroscopia de reflectância no VIS-NIR-SWIR, para a caracterização granulométrica de amostras de solos de diferentes classes texturais, e obter modelos de predição dos teores de argila, silte e areia no solo. Utilizou-se um conjunto de amostras representativas de Latossolos e Argissolo de cinco locais do Estado do Mato Grosso do Sul. Os espectros do visível e do infravermelho próximo ao infravermelho de ondas curtas (de 350 a 2.500 nm) das amostra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
1
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 26 publications
(41 reference statements)
3
15
1
9
Order By: Relevance
“…The medium texture was subdivided into medium clayey and medium sandy for evaluation purposes, a procedure that has been used in soil management ). Franceschini et al (2013) also reported significant differences among soils with different textures in laboratory and with hyperspectral sensing (FRANCESCHINI et al, 2015). Soil texture prediction through spectrum by terrestrial platform has shown to be more efficient (ARAÚJO et al, 2014) reaching R² 0.82.…”
Section: Estimative and Spatialization Of Topsoil Texturementioning
confidence: 99%
“…The medium texture was subdivided into medium clayey and medium sandy for evaluation purposes, a procedure that has been used in soil management ). Franceschini et al (2013) also reported significant differences among soils with different textures in laboratory and with hyperspectral sensing (FRANCESCHINI et al, 2015). Soil texture prediction through spectrum by terrestrial platform has shown to be more efficient (ARAÚJO et al, 2014) reaching R² 0.82.…”
Section: Estimative and Spatialization Of Topsoil Texturementioning
confidence: 99%
“…This program offers several options for data treatment to optimize the PCA. Various treatments were tested and the sequence that better featured the results in the transformation, in accordance to Franceschini et al [36], as follows: first, spectral transformation of reflectance data for absorbance; second, spectral data processing by SNV (Standard Normal Variate); third, transformation of spectral data by MSC (Multiple Scattering Correction); and, fourth, data smoothing by applying the Savitzky-Golay filter with second-order polynomial.…”
Section: Assessment Of Principal Component Analysis (Pca)mentioning
confidence: 99%
“…Franceschini et al (2013) señalan que para arcilla y arena se presentan picos en la región de 1200 nm, 1900 nm y 2200 nm debido a la presencia de filosilicatos (como caolinita) y gibsita para oxisoles y ultisoles en la región de Mato Grosso, Brasil. Para esta investigación, en esta región del espectro se manifiesta la caolinita.…”
Section: Colombia Forestalunclassified